Preserving Primate Paradises: Innovative Communication Risk Strategies For Deforestation Prevention In The Enchanting Mentawai Islands, Indonesia - Chania, Indah; Hidayat, Muhamad (SEAN Institute, 2024)
As one of the tropical countries in Southeast Asia, Indonesia boasts a remarkable diversity of flora that serves as a habitat for the wildlife within its borders. This diversity has positioned Indonesia as a nation with the highest diversity of primate species globally, comprising 61 species out of the 479 primate species worldwide, with 38 of them being endemic. The distribution of primate species in Indonesia extends from the far reaches of Papua to the tip of Sumatra, including the Mentawai Islands. Mentawai, known as a regency beyond the boundaries of Sumatra, is home to four endemic primate species: Bilou (Hylobates Klosi); Joja (Presbytis Potenziani); Monyet Ekor Babi (Simias Concolor); and Bokkoi (Macaca Pagensis). According to the International Union for Conservation of Nature (IUCN) Red List, these four species are currently listed as critically endangered due to deforestation activities leading to the loss of their habitats. This study aims to determine barriers and risk communication strategies in preventing deforestation (case study of biodiversity of four endangered endemic primates in Mentawai Islands, Indonesia). This research method uses descriptive qualitative research methods with data collection techniques using observation, interviews, documentation, and literature review.